Exploring desirable nature futures for Nationaal Park Hollandse Duinen. Issue 1 (31st December 2022) - Kuiper, Jan J.; van Wijk, Dianneke; Mooij, Wolf M.; Remme, Roy P.; Peterson, Garry D.; Karlsson-Vinkhuyzen, Sylvia; Mooij, Charlotte J.; Leltz, Georgette M.; Pereira, Laura M.
ABSTRACT: Achieving global sustainability goals requires most people and societies to fundamentally revisit their relationship with nature. New approaches are called for to guide change processes towards sustainable futures that embrace the plurality of people's desired relationships with nature. This paper presents a novel approach to exploring desirable futures for nature and people that was developed through an application in Nationaal Park Hollandse Duinen in the Netherlands. This new national park is developed bottom-up by a diverse group of actors reshaping their interactions with each other and with nature. Our approach, co-designed with key stakeholders of the national park, engages with a new pluralistic framework for human-nature relationships presented by the IPBES task force on scenarios and models to catalyze the development of nature-centered scenarios. We integrated this Nature Futures Framework with the Three Horizons Framework in a participatory workshop process designed to bring people's diverse relationships with nature to the fore, and jointly envision desirable futures and the pathways to get there. We present a methodology to analyze and compare the visions and assess their potential contribution to the SDGs. We summarize the results of the application in Nationaal Park Hollandse Duinen and reflect on lessons learned. The approach successfully engaged participants in joint exploration of desirable futures for the national park based on their plural perspectives on human-nature relationships. We see much potential for its applications to support change processes in various social-ecological contexts toward more sustainable futures for nature and people.